Mixed matrix membrane chromatography based on lewatit mp500 anion exchanger resin and lewatit cnp105 cation exchanger resin for whey protein fractionation - Siti Nor Ainda, Mazlan (2014)
The concept of mixed matrix membrane (MMM) chromatography is an alternative that provides a simple method for the preparation of adsorptive membranes, yet results in high quality membrane chromatography performance. MMMs are prepared by incorporating an ion exchange resin (or any adsorptive resin) into a membrane polymer solution prior to membrane casting. In this study, MMM will be prepared by combining cation and anion simultaneously in EVAL based polymer solution. The membrane will be used for whey protein fractionation to recover both acidic and basic protein. Whey is the liquid byproduct of casein precipitation of milk in the cheese or casein manufacturing industries and of milk concentration prior to milk powder production (Saufi, 2010). Rather than using the high cost ion exchange resin that purposely design for protein fractionation, this study will using a low cost ion exchanger resin that commonly used at the industry. The 7.5 wt% anion resin (MP500) will be bland with 7.5 wt% cation resin (CNP105) in the 15wt% EVAL based polymer solution. This mixed mode interaction MMM will applied for whey protein fractionation. The feasibility of MMM was tested in whey protein fractionation processes. WPI solutions were diluted to 2mg/mL with different pH binding buffer solution (pH 4, 5, 6, 7, and 8). The whey protein compositions after binding were assayed using UPLC column ACQUITY UPLC PrST using a C4 Jupiter column. A combination of pH and salt elution using different pH elution buffers will be performed to selectively elute the bound protein on the membrane. This membrane had a maximum static binding capacity of 0.260 mg/mL β-Lac, 0.214 mg/mL BSA, and 0.118 mg/mL α-Lac per membrane at pH 5. The membrane was successfully applied to bind acidic and basic proteins simultaneously from a mixture. Based on batch elution experimental results, a productivity of 0.156 mg whey protein mL-1 membrane h-1 was calculated using this customized mixed mode MMM